Memulihkan Kembali Identitas Gereja yang Eskatologis Melalui Word dan Sacrament Sebagai Dasar Pembentukan Spiritualitas Gereja - Heriono, Billiam; Candara, Rudi (Veritas : Jurnal Teologi dan Pelayanan, 2023)
The teaching or doctrine related to Christian eschatology is often considered unimportant or at least less important for various reasons: it is located in the last part of systematic theology, speculative, irrelevant, and often causes polemics in its interpretation. These reasons have led to the lack or even neglect of eschatology being taught and lived out in the liturgy and the life of the church. Therefore, through a literature study, the authors propose how the church today can recover its identity as an eschatological community as envisioned in the Scriptures. In particular, the author shows how the church can see and execute the proclamation of the Word and administer the sacrament of Holy Communion or the Eucharist eschatologically. The authors’ conviction is that an eschatological perspective and praxis in the church is an appropriate and healthy way to rebuild the spirituality of believers today.